Text-Atlas of Skeletal Age Determination : MRI of the Hand and Wrist in Children. - Tomei, Ernesto (Current clinical imaging., 2013)
Text-Atlas of Skeletal Age Determination: MRI of the Hand and Wrist in Children collects in a single volume all that is currently known and applicable about the use of magnetic resonance imaging (MRI) for the assessment of bone age. The radiographic examination of the hand/wrist was initially used to study skeletal development, correlating skeletal and chronological age in order to verify potential growth and whether a need for intervention was necessary. In recent years, the reasons for this examination have expanded beyond assessment of development, into such are.